2020
DOI: 10.1055/s-0040-1718577
|View full text |Cite
|
Sign up to set email alerts
|

Association of Delivery Room and Neonatal Intensive Care Unit Intubation, and Number of Tracheal Intubation Attempts with Death or Severe Neurological Injury among Preterm Infants

Abstract: Objective The study aimed to assess the association of tracheal intubation (TI) and where it is performed, and the number of TI attempts with death and/or severe neurological injury (SNI) among preterm infants. Study Design Retrospective cohort study of infants born 23 to 32 weeks, admitted to a single level-3 neonatal intensive care unit (NICU) between 2015 and 2018. Exposures were location of TI (delivery room [DR] vs. NICU) and number of TI attempts (1 vs. >1). Primary outcome was death and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The present study showed that EPT infants who were intubated in the delivery room had a higher risk of severe IVH and any grade IVH than those who were not. A retrospective cohort study in Canada showed that DRI was associated with higher odds of death and severe neurological injury compared with NICU intubation or no intubation among infants born at ≤ 28 gestational weeks 6 , which was consistent with our findings. A large retrospective cohort study in California showed that the differences in the results of DRI for severe IVH stratified by gestational age category (e.g., 24–25 gestational weeks, odds ratio 1.20, 95% CI 0.98–0.147; 26–27 gestational weeks, odds ratio 1.40, 95% CI 1.16–1.69) 5 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study showed that EPT infants who were intubated in the delivery room had a higher risk of severe IVH and any grade IVH than those who were not. A retrospective cohort study in Canada showed that DRI was associated with higher odds of death and severe neurological injury compared with NICU intubation or no intubation among infants born at ≤ 28 gestational weeks 6 , which was consistent with our findings. A large retrospective cohort study in California showed that the differences in the results of DRI for severe IVH stratified by gestational age category (e.g., 24–25 gestational weeks, odds ratio 1.20, 95% CI 0.98–0.147; 26–27 gestational weeks, odds ratio 1.40, 95% CI 1.16–1.69) 5 .…”
Section: Discussionsupporting
confidence: 91%
“…We selected potential confounders on the basis of previous studies 5 , 6 , 26 . Child factors included gestational age (24, 25, 26, and 27 gestational weeks; categorical), birth weight (< 500, 500–749, 750–999, and ≥ 1,000 g; categorical), small for gestational age (dichotomous), sex (dichotomous), multiple births (dichotomous), facility-level at birth (tertiary, secondary, and others; categorical), birth year (2003–2008, 2009–2014, and 2015–2019; categorical), Apgar scores at 1 and 5 min (0–3, 4–6, and 7–10; categorical), placental transfusion (dichotomous), and RDS (dichotomous).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence from retrospective analyzes that successful first attempt intubation is associated with less intra-ventricular hemorrhage (IVH) in very preterm infants ( 17 ). Others did not observe this association but found DR intubations to be associated with higher odds of death and severe neurological injury when compared to NICU intubations ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In theory, intubation in the delivery room generally suggests the newborn has a weak spontaneous breath or severe pulmonary diseases (such as severe RDS, and congenital diaphragmatic hernia). Consequently, intubation seems associated with many adverse outcomes during hospitalization [ 5 , 6 ]. Meanwhile, it has been described that pulmonary hemorrhage is caused by many triggers.…”
Section: Introductionmentioning
confidence: 99%